Implementation of the Merah Putih Urban Village Cooperative Program in Serang City - Nursyamsi, Amala; Agustino, Leo; Sjafari, Agus (Future Science, 2026)
The Merah Putih Village Cooperative Program is part of the government's national strategy to strengthen the local community-based people's economy through the establishment of cooperatives at the village and sub-district levels. This study attempts to explore the factual conditions of KKMP land acquisition in Taktakan District, of the 13 sub-districts, only 4 have recorded progress in the construction of KKMP outlets. Using the theoretical approach of Merielle S. Grindlle is expected to be able to reveal the content of policy and the implementation environment (Context of Implementation) of the KKMP Program in the villages in Taktakan District. First, Content of Policy (content of Policy) in general the planning and process of building KKMP outlets cannot be measured for their impact, but from the aspect of the content of the policy the output of KKMP development is only physical infrastructure or KMP management personnel. In fact, there is no KKMP outlet that has been 100% completed in Serang City. The content of the policy in the form of land and building standardization, this condition makes it difficult for several villages to procure land or select strategic locations for the construction of KKMP outlets. Second, Context of Implementation (Context of Implementation) although KKMP is a National Strategic Program (PSN) does not mean there are no obstacles in land acquisition, because budget support for land acquisition is not budgeted and the availability of land or state land to build KKMP in each village is also not all strategic locations.